Indian Wheat Genomics Initiative for Harnessing the Potential of Wheat Germplasm Resources for Breeding Disease-Resistant, Nutrient-Dense, and Climate-Resilient Cultivars - Kumar, Sundeep; Jacob, Sherry R.; Mir, Reyazul Rouf; Vikas, V. K.; Kulwal, Pawan; Chandra, Tilak; Kaur, Satinder; Kumar, Uttam; Kumar, Suneel; Sharma, Shailendra; Singh, Ravinder; Prasad, Sai; et al. (Frontiers in Genetics, 2022)
Wheat is a major staple cereal food crop in India. However, the production and productivity of wheat in India is hampered by various biotic and abiotic stresses. To ensure food security to the growing population in India, there is an urgent need to explore the untapped genetic diversity for development of stress-resistant cultivars. The improvement of any crop lies in exploring and exploiting the genetic diversity available in its genetic resources including cultivated forms, land races, wild relatives and related genera. A huge collection of these genetic resources are conserved in various gene banks across the globe. Characterization and documentation of these conserved genetic resources are prerequisite for the germplasm utilization in crop improvement. The National Gene bank of India has an extensive and diverse collection of wheat germplasm comprising of Indian wheat landraces, primitive cultivars, breeding lines etc. which can contribute immensely for the development of high level of biotic/abiotic stress tolerance in wheat cultivars. Breeding wheat varieties that may give high yield under different stress environment has not made much headway due to high genotype x environment interaction, non-availability of truly resistant germplasm and non-availability of reliable markers linked with the QTLs having significant impact on resistance. The development of new breeding technologies like genomic selection (GS), which take into account the G X E interaction, will facilitate crop improvement through enhanced climate resilience, by combining biotic and abiotic stress tolerance and maximized yield potential. In this article, we have summarized different constraints facing Indian wheat breeding programs, challenges in addressing the biotic and abiotic stresses, improving quality and nutrition. Efforts have been also made to highlight the wealth of Indian wheat genetic resources available in our gene banks and its evaluation for identification of trait specific germplasm. Promising genotypes for variety of important targeted traits and development of different genomics resources have been also highlighted.